Steuern in Fragilen Staaten: Empfehlungen für die Entwicklungszusammenarbeit - Hans-Georg Petersen (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 2010)
– Fragile states are characterized by institutions which do not have the political will or ability to reduce poverty in the interests of their citizen, to establish basic social security, to promote a successful development process, and to guarantee security and human rights. The regional disintegration processes after the period of imperialism and the fall of the iron curtain have created many new states, which still are politically unstable and unable for a sustainable development. In the literature such states are describes as weak, failing or failed, collapsed, conflict or post-conflict; - dependant on the extent of the particular state failure. Several indicators try to describe such states and partly allow for projections of the future development. Then the role of taxation is discussed in detail before recommendations for the development cooperation are presented. Obviously taxation plays a key role for the democratization process in fragile states.
urn:nbn:de:kobv:517-opus-48465
Keywords: H11; H20; F5; O1; O2; O57; P50; 330; fragile state; state theory; stable states; fragility index; taxation; shadow economy; tax administration; development cooperation; Politische Stabilität; Staatstheorie; Steuer; Steuererhebung; Demokratisierung; Entwicklungskooperation; Entwicklungsländer; Entwicklungshilfe